Molecular mechanisms of resistance and treatment efficacy of clofazimine and bedaquiline against Mycobacterium tuberculosis - Islam, Md Mahmudul; Alam, Md Shah; Liu, Zhiyong; Khatun, Mst Sumaia; Yusuf, Buhari; Hameed, H. M. Adnan; Tian, Xirong; Chhotaray, Chiranjibi; Basnet, Rajesh; Abraha, Haftay; Zhang, Xiaofan; Khan, Shahzad Akbar; et al. (Frontiers in Medicine, 2024)
Clofazimine (CFZ) and bedaquiline (BDQ) are currently used for the treatment of multidrugresistant (MDR) Mycobacterium tuberculosis (Mtb) strains. In recent years, adding CFZ and BDQ to tuberculosis (TB) drug regimens against MDR Mtb strains has significantly improved treatment results, but these improvements are threatened by the emergence of MDR and extensively drug-resistant (XDR) Mtb strains. Recently, CFZ and BDQ have attracted much attention for their strong clinical efficacy, although very little is known about the mechanisms of action, drug susceptibility test (DST), resistance mechanisms, cross-resistance, and pharmacokinetics of these two drugs. In this current review, we provide recent updates on the mechanisms of action, DST, associated mutations with individual resistance and cross-resistance, clinical efficacy, and pharmacokinetics of CFZ and BDQ against Mtb strains. Presently, known mechanisms of resistance for CFZ and/or BDQ include mutations within the Rv0678, pepQ, Rv1979c, and atpE genes. The cross-resistance between CFZ and BDQ may reduce available MDR-/XDR-TB treatment options. The use of CFZ and BDQ for treatment in the setting of limited DST could allow further spread of drug resistance. The DST and resistance knowledge are urgently needed where CFZ and BDQ resistance do emerge. Therefore, an in-depth understanding of clinical efficacy, DST, cross-resistance, and pharmacokinetics for CFZ and BDQ against Mtb can provide new ideas for improving treatment outcomes, reducing mortality,preventing drug resistance, and TB transmission. Along with this, it will also help to develop rapid molecular diagnostic tools as well as novel therapeutic drugs for TB.